PENGARUH GOOD CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP REAL EARNINGS MANAGEMENT (STUDI LINTAS NEGARA ASEAN) - Verawati Damayanti Manurung; Instianingsih Instianingasih (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
We examine Asean Corporate Governance and Quality Audit for analyzing Good Corporate Governance and Audit Quality to real earnings management, with control variable, Leverage, Size, Country and Country. Real Earnings Management calculate by three proxy, Abnormal cash flow, Abnormal Discretionary Expense and Abnormal Production. From 34 company of manufacture in Asean CG Scorecard Top 50 and Top 30 or Cross Country Asean during 2014 till 2016, we conclude Asean Corporate Governance, Quality Audit as Independent variable have impact to Real Earning Managements. Same as independent variable, all control variable, Leverage, Size, Country and Country also Impact to Real Earning Managements. It shown highest average point. Asean CG Scorecard from Thailand significant to real earning management